Management traffic in emerging remote configuration mechanisms for residential gateways and home devices. - Nikolaidis, Apostolos E.
XML technology is penetrating the network management in the IETF, UPnP, and DSL forum suite of standards and protocols. The advantages of XML are offered at the cost of long byte streams due to XML's inherently verbose nature. The increase in packet size for remote configuration and management can pose problems, if executed in a point-to-multipoint arrangement comprising one automatic configuration server and thousands of home gateways and multimedia devices. We investigate and exploit the repetitive nature of text patterns in typical XML documents as produced by the configuration and management tasks and as coded in SOAP RPCs. The solution mainly comes from application of the Lempel-Ziv compression algorithm, with minimal additions in the proposed DSL Forum standard. Numerical and experimental results support the applicability and advantages of the proposed approach and provide insight on how these are attributable to different layers of the employed protocol stack.
Keywords: Lempel-Ziv compression algorithm; XML technology; home device; home gateway; point-to-multipoint arrangement; protocol; remote configuration mechanism; residential gateway; traffic management; wide area network